A study to assess the emotional disorders with special reference to stress of medical students of Agartala government medical college and Govinda ballabh pant hospital - Taranga Reang; Himadri Bhattacharjya (Wolters Kluwer Medknow Publications, 2013)
Background: Stress is very common psychological phenomena where medical students faced in day to day activities. Epidemiological studies have asserted that about 70-80% of the diseases may be related to stress. Research related to this stress especially among medical students is essential, considering their learning, role and responsibilities as a future physician and health intervention programs. Objectives: To estimate the prevalence of stress and identify stressors among medical students. Materials and Methods: A Cross-sectional study was carried out among undergraduate medical students and self administered GHQ-12 and stressor questionnaire were used to collect information regarding stress. Binary logistic regression analysis was performed to calculate odds ratio (OR). Results: Prevalence of stress was 94.52% and more common among females. 33.56% students felt constantly under strain and 25.34% had loss of sleep over worry. Majority of the students of all semesters had stress (P > 0.05) and stressors viz. 'competition for marks' (P = 0.005), 'frequent examination' (P = 0.001), 'difficulty in finding time for recreation' (P = 0.014) and 'being away from home' (P = 0.027) were predominantly experienced by the 1 st year medical students. Multiple logistic regression analysis revealed the causal effect of main parameter on the GHQ caseness and students who found difficulties in following teaching language among the caseness had 81.59% higher chance of developing stress (OR = 8.159, CI = 1.228-54.213). Conclusion: The stress experience was more common due to academics and seen among all year of medical students. Strategy development for eliminating stressors is necessary for promoting healthy life.